The China-India Nuclear Crossroads - Saalman, Lora; Saalman, Lora (Carnegie Endowment for International Peace, 2012)
Global power is shifting to Asia. The U.S. military is embarking on an American "pivot" to the Indo-Pacific region, and the bulk of global arms spending is directed toward Asian theaters. India and Pakistan are thought to be building up their nuclear arsenals while questions persist about China's potential to "sprint to parity." China remains by far the world's largest market for new nuclear energy production, and India aspires to be on a similar trajectory. Despite these trends, The China-India Nuclear Crossroads is the first serious book by leading Chinese and Indian experts to examine the political, military, and technical factors that affect Sino-Indian nuclear relations. In this book, editor and translator Lora Saalman presents a comprehensive framework through which China and India can pursue enhanced cooperation and minimize the unintended consequences of their security dilemmas.